THE IMPORTANCE OF THE CONCEPTS OF INTERDISCIPLINARITY AND MULTIDISCIPLINARITY IN BACHELOR OF SCIENCE AND TECHNOLOGY COURSES - Rodrigues dos Santos, Dienes; Franco Campos da Mata , Jônatas (Journal of Interdisciplinary Debates, 2021)
Interdisciplinarity is an advocacy of multiple disciplines, not the elimination of curricular subjects, as one might mistakenly infer. In other words, a solid disciplinary base is a prerequisite for the development of interdisciplinary projects. At the same time, disciplines are historical products of scientific development, being epistemological tools of scientific practice and political institutional arrangements for the control of knowledge. The knowledge related to interdisciplinarity builds, in the social environment, a relationship established across disciplines, and can be inserted in schools through projects and comprehensive work. Such projects can be observed in some universities. The use of interdisciplinarity in science and technology courses offers precious opportunities for students to solve problems, effectively building and consolidating knowledge in a learning process capable of inserting them in the labor market. Like interdisciplinarity, multidisciplinarity is a catalyst in the teaching-learning process, enabling students to act actively in the construction of their knowledge. Multidisciplinarity means that several disciplines study the same subject at the same time. The present article was developed to present a qualitative and quantitative panorama of the courses of Interdisciplinary Bachelor of Science and Technology, offered in brazilian federal universities.